SKRINING FITOKIMIA DAN KANDUNGAN TOTAL FLAVANOID PADA BUAH Carica pubescens Lenne & K. Koch DI KAWASAN BROMO, CANGAR, DAN DATARAN TINGGI DIENG - Minarno, Eko Budi (El-Hayah : Jurnal Biologi, 2015)
Carica Â pubescens Lenne K. Koch is one of the species in the tropics, which adapt to the plateau environment and low temperatures. In Indonesia, this plant is found at Cangar, Bromo, and Dieng Plateau. This study aims to determine the results of phytochemical screening and total flavonoids in fruit samples were taken from the third place. Qualitative and quantitative tests carried out in the Laboratory of Department of Biology and Chemistry, Faculty of Science and Technology, Maulana Malik Ibrahim State Islamic University, Malang. Analysis of total flavonoids using a spectrophotometer at Î» = 510 nm. The results of qualitative phytochemical screening tests on samples of C. pubescens fruits at Cangar, Bromo, and Dieng Plateau shows that the positive sample contains flavonoids, polyphenols, tannins, and triterpenoids. Quantitative test results show that the C. pubescens at Cangar contains Â total flavonoids quercetin equivalent with value 800 mg / L, Bromo with value 816.65 mg / L, and Dieng Plateau with value 633.35 mg / L, respectively.